A systematic review of the efficiency of radiation protection training in raising awareness of medical staff working in catheterisation laboratory - Alahmari, M.; Sun, Zhonghua (Bentham Science Publishers B.V., 2015)
The purpose of this study is to conduct a systematic review of the efficiency of radiation protection (RP) training in minimising the radiation dose to both medical staff and patients. The literature search for the relevant articles was performed using five different databases which included Scopus, Science Direct, PubMed, Medline and ProQuest. The search covered English language publications in the period between 2000 and 2014. The search was also limited to peer-reviewed articles on human subjects and reporting patient doses, staff doses or both before and after RP training. The dose reductions were compared using percentage calculations. Ten articles met the inclusion criteria and were included in the study. Seven of these studies showed the value of the RP training by measuring the patient dose and the fluoroscopy time (FT) pre- and post-training, whereas the remaining two of the three studies focused on the occupational doses only and one reported patient and staff doses as well as the FT. After receiving training, a reduction was found in patient doses and FT with a mean and standard deviation of 49% ± 0.15 and 12% ± 0.15, respectively. Additionally, the analysis displayed an occupational dose reduction by a mean and standard deviation of 72% ± 0.14 after receiving training. This review shows the necessity and efficacy of RP training in order to provide a safer environment when utilising the fluoroscopic image-guided machines by medical staff working in the catheterisation laboratory.